Inclusive Digital Governance in Urban Settings: A Case Study of the Adminduk Smart Service in Samarinda (Universitas Terbuka, 2025)
Digital transformation plays a vital role in the modernization of urban governance. Nevertheless, the success of digitalization is not only determined by the power of technology, but also by its ability to ensure equal access and participation from society. This study aims to analyze the implementation of Adminduk Smart Service within the framework of the principles of Inclusive Urban Digital Governance. With a qualitative approach through observations and interviews, the analysis is focused on the implementation of Adminduk Smart Service services, its alignment with the principles of Inclusive Urban Digital Governance and examining institutional challenges in the implementation of Adminduk Smart Service. These findings show that Adminduk Smart Service is a website-based population administration service that aims to expand the reach and access of services in Samarinda.. In addition, there is an integration of digital services with urban village counters to reach people who have technological limitations. However, there are still challenges such as differences in perception between officers and technological capacity in providing services. This research provides a conceptual contribution to inclusive and responsive digital governance in public administration.